Examining the Effects of Service Quality, Customer Satisfaction, and Marketing Communication on Customer Loyalty in Consumer Finance - Budhi Heriyanto, Agustinus Yanuar; Helena Louise Panggabean (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
The consumer finance industry in Indonesia has become increasingly competitive due to the rapid growth of non-bank financial institutions and the widespread adoption of digital technology. The increasingly intense competition in the financial services industry requires companies to deliver high-quality services efficiently in order to enhance customer satisfaction and loyalty. In the context of consumer finance, rapid business expansion is often prioritized, while critical factors such as service quality, customer satisfaction, and effective marketing communication receive less attention. However, these factors play a crucial role in sustaining long-term customer loyalty and competitive advantage. This study aims to examine the effects of service quality, customer satisfaction, and marketing communication on customer loyalty in the consumer finance sector. Data were collected using a structured questionnaire administered to 100 customers of a consumer finance company in Indonesia. Multiple linear regression analysis was employed, along with tests of the coefficient of determination and hypothesis testing using SPSS 26.0. The results indicate that service quality, customer satisfaction, and marketing communication have a significant and positive effect on customer loyalty, with an adjusted R² value of 69.8%. The t-test results confirm the individual significance of each independent variable, while the F-test demonstrates the overall robustness of the regression model. These findings highlight the importance of strengthening service quality, enhancing customer satisfaction, and implementing effective marketing communication strategies to foster customer loyalty in the consumer finance industry.